(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A feeding trial was carried out to study the effects of sorghumtannin on the performance and carcass characteristics of broiler chicks.Seven experimental diets were formulated using zero tannin maize ascontrol and six sorghum grain varieties, each two with low, medium andhigh tannin level. Diets were fed to 196 unsexed Hubbard commercialbroilers chicks for 5 weeks. Low tannin Safra had the best amino acidscomposition followed by high tannin sorghum varieties. Broilersperformance and carcass characteristics showed inconsistent trend as thelevel of tannin increased, since the birds consuming sorghums with hightannin content gave better performance than their counterparts fedmedium tannin. In addition, the results showed that sorghum varietieswith the same tannin level gave different effects on broiler performanceand carcass characteristics. These results indicate that, tannin level maynot be the sole factor affecting nutritional quality of sorghum grains; otherfactors may be involved.